STEM NASA Undergraduate Research in a Minority - Serving Community College (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The paper analyses undergraduate research in a minority - serving community college and provides an example of a specially developed mathematics program aimed at academic preparation leading to the increase of the efficiency of the following field work at the NASA premises.